ISSUES OF ELECTRONIC ASSESSMENT OF THE EFFECTIVENESS OF THE ACTIVITIES OF MEMBERS OF THE SUPERVISORY BOARD AT STATE ENTERPRISES - Tashmatov, Rustam (Science technology&Digital finance, 2023)
This article presents the main methods and methods for assessing the effectiveness of the activities of members of the board of directors (supervisory board) at state-owned enterprises, summarizes the general rules and results of these assessments, and also gives suggestions for the possibility of using this practice in Uzbekistan.